JURIDICAL REVIEW REGARDING THE MAKING OF HALAL CERTIFICATION FOR MSMES IN SANGATTA CITY - Radhitya, Atthyya; Yuniarsih; Azizah, Rizqi Amalia (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The majority of Indonesia's population is Muslim, so the halalness of a product is very important, especially for products that enter the body. Therefore, the Government, through several regulations, has implemented a policy, namely implementing mandatory halal certification for every MSME actor as stated in Article 2 paragraph (1) of Government Regulation no. 39 of 2021 concerning Implementation of Halal Product Guarantee Sector. However, there are many polemics among MSME players regarding halal certification, starting from limited knowledge regarding how to register, limited costs if it is necessary to register for halal certification, and also minimal outreach regarding the importance of halal certification for MSME players in Sangatta city . In order to overcome these obstacles, collaborative efforts are needed between the government, related institutions and MSME actors themselves. Concrete steps that can be taken include increasing outreach and education, providing cost subsidies, simplifying the certification process, strengthening coordination between related institutions. In this journal, it is appropriate to use normative methods with statutory and conceptual approaches. This halal certification has a very important role in increasing consumer confidence, product competitiveness and access to global markets.